PROTEOMICS IN MEAT SCIENCE — CURRENT STATUS AND FUTURE PERSPECTIVE - Galia Zamaratskaia; Shengjie Li (Теория и практика переработки мяса)
The aim of proteomics is to identify all proteins, their biological activity, post-translational modiﬁcations and interactions in a cell, and to identify (quantify?) changes in «proteome» in response to altered biological conditions. A typical proteomics work ﬂow consists of protein extraction, separation, protein or peptide identiﬁcation and data analysis. Mass spectrometry is the most common method used to detect proteins or peptides in proteomics. This strategy has many applications, including research in meat science, but it is limited by huge biochemical heterogeneity of the proteins and an inability to detect accurately low-abundance proteins. The aim of the present review is to summarize the current knowledge and identify future potential application of proteomics in meat science and technology.